IMPLEMENTASI DIGITAL MARKETING DALAM ERA SOCIETY 5.0 - Desi Jelanti; Meta Nursita; Napisah Napisah; Khusnul Khuliqi; Nugroho Widhi Pratomo (LPPM Universitas Pamulang, 2021)
Digital marketing becomes a new prima donna in the business world is not without reason, digital marketing has some value more when compared to other promotional strategies. With the use of digital marketing manufacturers can market their products faster, easier, cheaper and also with a much wider reach because the virtual world seems to know no borders and time. Indonesia is